Authentic Leader and Employee’s Silence Behavior: Testing a Happiness at Work Mechanism - Muhammad Rasyid Abdillah; Rizqa Anita; Agusanto Agusanto; Adi Rahmat (Forum Inovasi Bisnis dan Manajemen, 2022)
A study that tries to explain more deeply the mechanism underlying the relationship between authentic leadership and silence behavior has not been explored. Hence, the study trying to investigate it is still needed. This study endeavor to explain the relationship between authentic leadership and subordinates’ silence behavior. Specifically, this study utilized happiness at work as a psychological mechanism underlying the relationship between the two variables. The current study involved 310 full-time worker who work as government officers in government institutions in a province in Indonesia and used PLS-SEM analysis to test hypotheses. The study finding revealed that authentic leadership has a negative effect on subordinates’ silence behavior. Furthermore, this study also revealed that happiness at work mediates the relationship between authentic leadership and subordinates’ silence behavior. The study finding provides advanced knowledge about the function of authentic leadership in organizations to shapes positive attitudes and prevents negative behaviors, such as silence behavior..